Backward martingale transport and Fitzpatrick functions in pseudo-Euclidean spaces - Kramkov, D; Sîrbu, M (Institute of Mathematical Statistics, 2024)
We study an optimal transport problem with a backward martingale constraint in a pseudo-Euclidean space S. We show that the dual problem consists in the minimization of the expected values of the Fitzpatrick functions associated with maximal S-monotone sets. An optimal plan γ and an optimal maximal S-monotone set G are characterized by the condition that the support of γ is contained in the graph of the S-projection on G. For a Gaussian random variable Y, we get a unique decomposition: Y = X + Z , where X and Z are independent Gaussian random variables taking values, respectively, in complementary positive and negative linear subspaces of the S-space.